THE INFLUENCE OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON TEACHER JOB SATISFACTION AT SMPN 13 BOGOR CITY - Amanda, Sifa Saskia; Firdaus, Muhamad Azis; Subakti, Jani (Manager : Jurnal Ilmu Manajemen, 2025)
The purpose of this study is to ascertain how the work environment and leadership style of school principals at SMP Negeri 13 Bogor City affect teachers' job satisfaction. The methodology of this research is quantitative. To collect data, a questionnaire was distributed to all 34 teachers in the population, creating a saturated sample. Validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and determination coefficients are used to examine the data collected. With an r value calculated higher than 0.338 in the r table, the validity test findings indicate that each item on the questionnaire is valid. According to the reliability test, the Cronbach Alpha value of each variable is higher than 0.6, so the data is declared reliable. In part, the leadership style has a correlation value of 0.402 with a significance of 0.018 <0.05, and a correlation coefficient of the work environment of 0.567 and a significance level of 0.000 <0.05. Simultaneously, the determination coefficient (R²) is 0.432, the F test with an F value calculated as 11.806> the F table is 3.30 with a significance value of 0.000 <0.05, then Ho3 is rejected and Ha3 is accepted. According to the findings of the study, the job satisfaction of teachers of SMPN 13 Bogor City is positively and significantly influenced by their leadership style and work environment.